Days of glory: an analysis of Octavian’s triple triumph in 29 B.C. - Cunha, Macsuelber de Cássio Barros da (Romanitas - Revista de Estudos Grecolatinos, 2020)
In August of 29 BC, Rome witnessed a great event, the triumph of Octavian. A ceremony that exalted the victories of the Imperator Caesar and of his troops and exhibited the conquered riches. The triumphal procession linked past, present, and future. It was connected, in its origin, with the founder of Rome and first triumphator, Romulus; it celebrated in the present moment the victories of the triumphator general, exhibiting the vanquished peoples and the riches brought as war booty; and inscribed the name of the victor in the memory of future generations, both for the achievement, and for the memorable triumph that went through the streets of Rome, as well as for the monuments and / or buildings that could be erected with the war booty. In this work we analyze this great event and its relations with the architecture and the memory.